Genotypic and phenotypic characterization of G6PD deficiency in Bengali adults with severe and uncomplicated malaria - Katherine Plewes (2018)
© 2017 The Author(s). Background: Control of malaria increasingly involves administration of 8-aminoquinolines, with accompanying risk of haemolysis in individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency. Few data on the prevalence and genotypic basis of G6PD deficiency are available from Bangladesh, where malaria remains a major problem in the South (Chittagong Division). The aim of this study was to determine the prevalence of G6PD deficiency, and associated G6PD genotypes, in adults with falciparum malaria in southern Bangladesh. Methods: G6PD status was assessed via a combination of fluorescent spot testing (FST) and genotyping in 141 Bengali patients admitted with falciparum malaria to two centres in Chittagong Division from 2012 to 2014. In addition, an analysis of genomic data from 1000 Genomes Project was carried out among five healthy Indian subcontinent populations. Results: One male patient with uncomplicated malaria was found to have G6PD deficiency on FST and a genotype associated with deficiency (hemizygous Orissa variant). In addition, there were two female patients heterozygous for deficiency variants (Orissa and Kerala-Kalyan). These three patients had a relatively long duration of symptoms prior to admission compared to G6PD normal cases, possibly suggesting an interaction with parasite multiplication rate. In addition, one of 27 healthy local controls was deficient on FST and hemizygous for the Mahidol variant of G6PD deficiency. Examination of 1000 Genomes Project sequencing data across the Indian subcontinent showed that 19/723 chromosomes (2.63%) carried a variant associated with deficiency. In the Bengali from Bangladesh 1000 Genomes population, three of 130 chromosomes (2.31%) carried deficient alleles; this included single chromosomes carrying the Kerala-Kalyan and Orissa variants. Conclusions: In line with other recent work, G6PD deficiency is uncommon in Bengalis in Bangladesh. Further studies of particular ethnic groups are needed to evaluate the potential risk of wide deployment of primaquine in malaria control efforts in Bangladesh.